2022
DOI: 10.1038/s41467-022-29817-0
|View full text |Cite
|
Sign up to set email alerts
|

Towards actinide heterostructure synthesis and science

Abstract: Controlling dimensionality and strain in actinide heterostructures will provide unrivaled opportunities for exploring novel quantum phenomena. We discuss the promises, challenges, and synthesis routes for these actinide-bearing heterostructures with complex electron correlations for functional and energy materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…73 Thomas et al 71 suggested employing strong light-matter coupling to realize all-optical control of darkness and phase. Topological darkness was realized even in extremely thin 2D atomic layers under appropriate conditions 74 and was shown to be useful for the tasks of biosensing. In a separate development, tunable darkness was demonstrated for exceptional point.…”
Section: Darkness For Phase Detection and Enhanced Phase Sensitivity ...mentioning
confidence: 99%
“…73 Thomas et al 71 suggested employing strong light-matter coupling to realize all-optical control of darkness and phase. Topological darkness was realized even in extremely thin 2D atomic layers under appropriate conditions 74 and was shown to be useful for the tasks of biosensing. In a separate development, tunable darkness was demonstrated for exceptional point.…”
Section: Darkness For Phase Detection and Enhanced Phase Sensitivity ...mentioning
confidence: 99%
“…Extending heterostructure growth to actinide-based compounds therefore promises to enable researchers to study these materials in new ways. For example, low-dimensional heterostructures composed of actinide materials with 5f electrons, grown with interfaces containing tailored defect densities, represent a fertile area for the discovery of various emerging phenomena [253]. Studies have predicted a range of exotic physics for such structures, including highly correlated electron interactions [202,254], topological insulator behavior [207,210], and confined 2D properties [255,256].…”
Section: Future Directions: Thin Film Heterostructure Synthesis and C...mentioning
confidence: 99%
“…Extending heterostructure growth to actinide-based compounds therefore promises to enable researchers to study these materials in new ways. For example, low-dimensional heterostructures composed of actinide materials with 5f electrons, grown with interfaces containing tailored defect densities, represent a fertile area for the discovery of various emerging phenomena [241]. Studies have predicted a range of exotic physics for such structures, including highly correlated electron interactions [190,242], topological insulator behavior [195,198], and confined 2D properties [243,244].…”
Section: Future Directions: Thin Film Heterostructure Synthesis and C...mentioning
confidence: 99%